Micro-irrigation in India – present status and future prospects - Gurjar, D. S.; Khodke, U. M.; Kaur, Ravinder (Indian Farming, 2018)
Micro-irrigation is a modern method of irrigation having a great potential to achieve higher cropping and irrigation intensity with a significant impact on resource saving, cultivation cost, crop yied and farm productivity. Micro-irrigation has covered an area of about 4 million hectares in India and can be extended upto an area of about 42 million hectares. Micro-irrgation will certainly develop new farm practices and innovations with support of government have enhanced the income of famers and ensure the sustainability of agriculture in near future.